2007
DOI: 10.1249/mss.0b013e3181484d0e
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Gallbladder Disease Determined by Ultrasonography

Abstract: Physical activity seems to be significantly and inversely related to the development of gallbladder disease as assessed by ultrasonography in a population at high risk for gallbladder disease. These findings add to the evidence supporting a causal link between physical activity levels and a decreased risk of gallbladder disease, and they provide yet another reason to encourage the achievement and maintenance of a physically active lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 18 publications
3
30
0
2
Order By: Relevance
“…Long-term exposure to many risk factors, as is true for the elderly, may increase the risk of gallstone disease. At the same time, sedentary activity, which is greater in the elderly than in younger populations, may also increase the risk of gallstone disease [21,22] . Furthermore, gallstone disease is also an acquired disease influenced by chronic environmental factors plus an aging effect [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Long-term exposure to many risk factors, as is true for the elderly, may increase the risk of gallstone disease. At the same time, sedentary activity, which is greater in the elderly than in younger populations, may also increase the risk of gallstone disease [21,22] . Furthermore, gallstone disease is also an acquired disease influenced by chronic environmental factors plus an aging effect [23] .…”
Section: Discussionmentioning
confidence: 99%
“…In all, 11 of 19 cross-sectional analyses, including the five most recent studies [63][64][65][66][67] and the four investigations based on the largest population samples [57,58,66,67] found a significant preventive value in regular physical activity. Possibly, the absence of effect in the remaining eight studies could reflect a smaller sample size and/or a weaker assessment of habitual physical activity.…”
Section: Cross-sectional Analyses Of Habitual Physical Activity and Gmentioning
confidence: 99%
“…Kriska et al [64] carried out a 3-to 4-year prospective trial of 2130 American Indians who were initially free of gallstones, undertaking ultrasonography at follow-up; 650 of this sample developed gallbladder disease. After adjusting for confounders, including BMI, disease was inversely Banim et al [66] carried out a large-scale, 14-year prospective trial of 25,639 volunteers aged 40-74 years, evaluating the risk of developing gallstones against an initial four-level categorization of occupational and leisure physical activity.…”
Section: Cross-sectional Analyses Of Habitual Physical Activity and Gmentioning
confidence: 99%
“…However, prospective cohort studies provide more accurate information on physical activity, as this is measured before the development of disease and consequently is not subject to recall biases inherent in case-control studies. The published cohort studies have reported higher levels of physical activity reducing the risk of symptomatic gallstones by approximately a third [20][21][22][23][24]. However, a limitation of all these investigations was that the method for measuring physical activity, namely questionnaires had not been validated against detailed physiological measures of physical activity including energy expenditure and cardiorespiratory fitness.…”
Section: Introductionmentioning
confidence: 99%